The Bertrand Paradox, the Useless Auctioneer and the Launhardt Model1. (December 2014) - Lambertini, Luca; Mosca, Manuela
Abstract : We revisit the Cournot–Bertrand debate in the light of Cournot, Edgeworth and Launhardt, tracing back to Launhardt the origin of price competition in duopoly models with constant returns to scale. Then, we discuss the formalisation of consumer utility function for differentiated products, first appearing in Launhardt and then in Bowley. This allows us to point out that assuming that firms know the demand function(s) is equivalent to assuming that they know the structure of consumer preferences. Therefore, we argue that there is no role for the auctioneer, either in Cournot or in Walras.